(untitled) (Journal of the College of Basic Education, 2026)
The current research aimed to identify the concept of duration among kindergarten children, and it consisted of a real research of (100) children of a mature age (5-6) years, with (50) children and (50) children in the former first Karkh Directorate in Baghdad, and to achieve the goals of the research on a research tool with effective numbers with the age group that consists of (22) paragraphs and reached a study after statistical intelligences There are differences with a statistical choice of the sample in light of the research results that there are no statistically significant differences with regard to gender change.